Latin America Is the Region with the Lowest Productivity Growth in the World Since the Neoliberal Reforms. the New Middle Income Trap: Easy Rents Do Not Exactly Generate Schumpeterian Elites; [Latinoamérica Es la Región Con el Menor Crecimiento de la Productividad en el Mundo Desde Las Reformas Neoliberales. la Nueva Trampa del Ingreso Medio: Rentas Fáciles No Generan Precisamente Élites Schumpeterianas] - Palma-Penco, J (Fondo de Cultura Economica, 2022)
The “middle-income trap” in Latin America is about its inability to redesign productive strategies when the existing ones have become exhausted. Indolent elites, accustomed to living off “easy rents”, and neophobic states have become again the main obstacle to change. It already happened during the period of import substitution, and it is now happening again when the merely extractive model in the South of the region and the assembly model in the North have become exhausted. Instead of reigniting productivity growth by adding value to primary exports and strengthening backward linkages in extractive activities in one, or of “deepening” assembly manufacturing in the other—along with transforming “the green issue” into a new engine of productivity growth—what continues to prevail in the region is the “more of the same but, hopefully, better”, preached by orthodox economists and reinforced by new “investment-protection” treaties. All of this traps the region in an interregnum where the old fades away (since it gave all it could offer), but the new fails to be born—a scenario I have called our “Gramscian moment”. Despite a diversity of new progressive discourses, in Latin America (as in Hotel California), “we are all just prisoners here, of our own device”, with our social imagination still trapped in the “absolute certainties” of the still hegemonic neoliberal ideology—as if the region was in a state of addiction to an impoverished life. Perhaps this is what the young, women, and native people rebelled against in Chile in the social outbreak of October 2019. © 2022 Fondo de Cultura Economica. All rights reserved.